PERAN KPU DALAM PENCAPAIAN TARGET PARTISIPASI PEMILIH PADA PEMILIHAN KEPALA DAERAH KABUPATEN KARAWANG TAHUN 2015 - Kamal, Ahmad Mustopa; Rofieq, Ainur (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The background of this research is based on the efforts of the KPU of Karawang Regency in achieving the target of voter participation in the election of the Regional Head of Karawang Regency in 2015, where the KPU targets community participation around 72%. But from the results of the KPU recapitulation in Karawang Regency voter participation reached 67%. This indicates that the target of voter participation from the KPU of Karawang Regency was not achieved in the election of the regional head. This study uses descriptive analysis method to focus on a specific problem in detail. The focus of the research is: KPU's efforts in achieving the target of community participation in the Karawang District Election especially in Cibuaya District, Karawang Regency. The results of this study indicate that in planning achievement of voter participation target in the Karawang regency elections in 2015 Karawang Regency KPU did various things to direct voter participation, especially in terms of planning. Thus the role of the KPU in achieving the target of voter participation in the election of the Regional Head of Karawang Regency in 2015 in the District of Cibuaya has been done well.